Museums as primary tourist attractions in the function of the general development in the region - Владимир Кривошејев (Mенаџмент у хотелијерству и туризму, 2015)
Since the nineteenth century, with the massive founding of new institutions, museums also have had a great importance in the independent parallel process of the rapid development of tourist activity - they have been primary tourist attractions bringing a growing number of travellers to a certain destination. With the further tourism development directed towards the „ready-made“ massive offer of the type 3S, but also with the crisis of museums caused by not accepting general changes influencing modern needs of the public, the importance of the museum has decreased and they have become secondary and tertiary tourist attractions, the places that are less and less visited, and often visited without a prior intention. The pathways of the development of a museum and tourist activity crossed once again during the last decades of the twentieth century, when the parallel development of new museology and new tourism brought museums again in the focus of tourist trends. The aim of this paper is to show, on the basis of the analysis of the information from  the available relavant literature indicating modern trends and examples of good practice, that in the current connecting museum and tourist activitities museums are becoming primary tourist attractions again. This is indicated by the examples of big, classical world museums, like The Louvre and The British Museum, but also the museums in smaller towns like Belfort (France), Rotorua (New Zealand) and Dolny Kubin (Slovakia). The additional aim of the paper is to indicate, on the examples of The Gugenheim Museum in Bilbao and the branch of The Louvre in Lens, that the museums as primary tourist attractions can also be strategically designed generators of the exhausted economy renewal.